Strategi Untuk Mengatasi Rasa Insecure Pada Siswa Kelas 10 PPLG (Pengembangan Perangkat Lunak dan Gim) B di SMK Negeri 5 Surakarta - Pipit Nopiyanti; Rantri Mustika Dewi; Mellani Agustin (Institut Nalanda, 2023)
Insecurity is a feeling of discomfort felt by individuals, especially when they feel worried and lack of confidence, so that someone who experiences this will feel insecure and they will feel afraid in any condition and at any time. These feelings can occur when a person feels inadequate, guilty, ashamed, or unable to control something. And cause that person to be afraid to interact with others. The methods in this research are lectures and discussions. The informants or subjects in this research are 10th grade PPLG (Pengembangan Perangkat Lunak dan Gim) B students at SMK Negeri 5 Surakarta. The result of the research carried out by the resource person is to provide socialization related to how to overcome insecurity. The conclusion of the research carried out by the resource person can be that adolescents are vulnerable to insecurity, and must be given education on how to overcome this insecurity.